Effectiveness analysis and value incommensurability - Anders Herlitz (Cost Effectiveness and Resource Allocation)
Abstract This paper argues that in many contexts where effectiveness analysis such as benefit-cost analysis and cost-effectiveness analysis is used, we have good reason to think that some benefits or costs are incommensurable in value such that neither can be determined to be better than the other, although they cannot be determined to be equally good either. Two responses to such value incommensurability are outlined: abandoning conventional ways of measuring benefits and costs and replacing one-dimensional measures with multi-dimensional measures or sticking to conventional ways of measuring benefits and costs and accepting that whatever valuation one comes up with, it will fail to reflect the actual values and value relations between benefits and costs. Both responses are argued to be problematic.